Personal and Societal Influence in Career Choices and Pathways among Graduate Nurses in Low and Medium-Income Countries: A Case Study of Pwani University, Kenya - Omwenga, S; Amimo, F; Mbuthia, N; Ondieki, J (International Journal of Psychology, 2023)
Purpose: While nurses comprise a significant component of human resource for health (HRH), their shortages, especially in low- and middle-income countries (LMICs), have greatly contributed to the persistent poor health outcomes and poor progress towards attaining universal health coverage. There is limited understanding of personal and societal factors that influence graduate nurses' decisions when choosing a career path in nursing after training, especially in LMICs. Understanding how these graduate nurses decide on their career path is critical in informing future policies on attraction and retention in PHC. Methodology: An empirical study established graduate nurses' career choices and pathways trained at Pwani University, Kenya. Quantitative and qualitative data collection involved an online self-administered questionnaire followed by individual in-depth interviews of selected participants to better understand the experiences behind their career choices. Findings: From the study, there was a significant statistical relationship between respondents' university entry status and current job (p= 0.02). Majority of those who had direct entry were in private sector (42%) while majority of those who upgraded were in public sector (24%). The study results show that mentorship (58.9%) and parental influence (33.9%) were significant factors that influence career choices. Other factors that motivate individuals to choose nursing include the love of the physical nature of the profession, a desire to be part of a noble profession, exposure to caregiving, relatives in the nursing profession, and previous experiences with illness. The study also showed that most nurses work in hospital services and prefer urban locations due to the availability of personal growth opportunities and job prospects. Unique Contribution to Theory, Practice and Policy: A unique finding in this study is that work location is a strong determinant in attraction and retention especially for graduate nurses working in public facilities. The study therefore recommends offering personal growth opportunities and incentives for nurses working in rural and remote areas to increase nurse attraction and retention in public healthcare. The current study further recommends a longer cohort follow-up study to be conducted, incorporating larger sample sizes from various settings to compare pertinent influencing factors among these groups.